Navigating end-user perceptions: development and initial psychometric properties of a water quality perception scale - Nelson, Toby N. T.; Poleacovschi, Cristina; Weems, Carl F.; Ikuma, Kaoru; García, Ivis; Rehmann, Chris R. (Frontiers in Water, 2024)
Consistent and accurate measurement of public perceptions of water quality is useful for understanding water use behaviors, policy development/support, and community engagement, all essential for sustainable water management. Toward consistent and accurate measurement, we refined and examined the initial psychometric properties of a Water Quality Perception Scale (WQPS). In this study, we report an exploratory factor analysis (EFA) with 18 items on a group of respondents (N=154), which identified one primary factor, 'Individual Water Quality Perception,' consisting of 13 items and two additional factors represented by the remaining 5 items. Subsequently, a confirmatory factor analysis (CFA) was performed with (n=147 participants), including both original (n=74 assessed at a separate time from their original assessment) and new participants (n=73). The results of the CFA affirmed the initial loadings of the 13item WQPS in a single factor. The scale demonstrated internal consistency, with coefficients of 0.93 and 0.90 (Cronbach's alpha) in the two samples, and the measure showed convergent validity with the Household Water Insecurity Experiences Scale (HWISE), (r = -0.41 and -0.49 in the respective samples). This scale holds promise toward consistent and accurate measurement instrument for researching public perceptions of water quality, guiding policy and public initiatives to improve water management strategies.Avenues for further development and use are discussed.